Safe guarding date palm from oryzaephilus surinamensis infestation through oil palm inflorescence ash and hermetic storage technique treatments and the combination of both treatments (2013)
Possible control of Oryzaephilus surinamensis infestation on date palm (Phoenix dactylifera) using oil palm inflorescence ash and hermetic storage technique combined with Oil Palm Inflorescence Ash (OPIA) treatment were conducted in the Entomology Laboratory, Department of Zoology, University of Ibadan, Oyo state, Nigeria. Relative efficacy of oil palm inflorescence ash at 0.625 g /25 g and 1.25 g /25 g and 3 bags layer hermetic storage technique combined with oil palm inflorescence ash 0.625 g/25 g and 1.25g/25 g were tested on pristine and simulated date. The experiments were laid out in a completely randomized design and each treatment replicated four times for 5 and 10 weeks exposure periods. Result showed that oil palm inflorescence ash recorded adult mortality of (10.00±0.00)and (9.00±0.41) at 1.25 g, while (8.00±1.68) and (7.00±0.71) were recorded at 0.625 g after five weeks of exposure on both pristine and simulated date respectively. At 1.25 g concentration, reductions in larval and adult emergence were recorded. Combination of 3 bags layer hermetic storage technique with oil palm inflorescence ash treatment was highly effective with higher adult mortality, lower larval and adult emergence. Combined treatment of oil palm inflorescence ash and hermetic storage technique was found to have significant difference when compared to only oil palm inflorescence ash treatment at p<0.05, ANOV A. It is evident from this study that it may be necessary to combine hermetic storage technique with oil palm inflorescence ash to achieve a more effective control on dried date palm against O. surinamensis infestation during storage for a storage period often weeks.